Bortezomib Against Refractory Antibody-Mediated Rejection After ABO-Incompatible Living-Donor Liver Transplantation: Dramatic Effect in Acute-Phase? - Tajima, Tetsuya (Transplant Direct, 2019)
Antibody-mediated rejection (AMR) is a refractory rejection after donor-specific antibody-positive or ABO blood-type incompatible (ABOi) organ transplantation. Rituximab dramatically improved the outcome of ABOi living-donor liver transplantation (LDLT); however, an effective treatment for posttransplant AMR, once occurred, is yet to be established. A 44-year-old woman with biliary cirrhosis underwent ABOi-LDLT from her sister (AB-to-A). Pretransplant rituximab diminished CD19/20-positive B lymphocytes to 0.6%/0.0%; however, AMR occurred on posttransplant day-6 with marked increase in both CD19/20 cells (17.1%/5.8%) and anti-B IgM/G-titers (1024/512). Despite rituximab readministration, steroid-pulse, intravenous immunoglobulin, and plasmapheresis, AMR was uncontrollable, with further increasing CD19/20 cells (23.0%/0.0%) and antibody-titers (2048/512). Bortezomib (1.0 mg/m(2)) was thus administered on posttransplant day-9, immediately ameliorating CD19/20 cells (1.3%/0.0%) and antibody-titers (<256/128). Complete remission of refractory AMR was obtained by just 2 doses of bortezomib. Her liver function has been stable thereafter for over 3 years. This case highlighted the efficacy of bortezomib against refractory AMR after ABOi-LDLT. Unlike previous reports, the efficacy was very dramatic, presumably due to the administration timing near the peak of acute-phase AMR.